The Impact of Water Infrastructure, Home Ownership, and Educational Facilities on Economic Growth in East Java - Supiandi Supiandi (Yayasan Ghalih Pelopor Pendidikan, 2024)
This study examines the influence of three key infrastructure variables—water facilities, home ownership, and educational infrastructure—on economic growth in East Java, Indonesia, from 2015 to 2018. Using panel data regression analysis, the study explores both short-term and long-term impacts of these variables on economic output, measured by GRDP at constant prices. The fixed effect model results indicate that water infrastructure positively and significantly influences economic growth, while educational infrastructure shows a positive but marginally significant effect. Conversely, home ownership infrastructure has a significant negative impact on GRDP. These findings suggest that while water and educational infrastructure are vital drivers of regional economic development, policies should address inefficiencies related to home ownership to ensure balanced growth. The study underscores the critical role of infrastructure investment in driving economic performance in developing regions